CLINICAL CASE OF TREATMENT OF A PATIENT WITH CHRONIC MYELOID LEUKEMIA WITH A MUTATION BCR-ABL Y253H AND COMORBIDITIES - G. Sh. Safuanova; N. R. Ryabchikova; G. A. Gaisarova; E. G. Tsareva; D. R. Safuanova (Архивъ внутренней медицины, 2019)
The article presents information on the methods of diagnosis and targeted therapy of chronic myeloid leukemia (CML). A clinical case of CML with the development of resistance to therapy with 1st generation tyrosine kinase inhibitors (ITK), the appointment of 2nd generation ITK (dasatinib) with regard to comorbidity, the development of adverse events in the form of fibrosing alveolitis and severe pleurisy, translation of nilotitis in the form of fibrosis of the alveolitis and severe pleurisy is considered, but the lack of effect of treatment. The study of the mutational status revealed a BCR-ABL Y253H mutation, which made it possible to individualize the patient’s therapy, obtain a large molecular response, and overcome undesirable phenomena. The development of resistance or the loss of response to the treatment of ITK in CML with comorbidity requires the timely identification of mutations in the kinase domain of BCR-ABL and contributes to the selection of early personalized therapy for a particular patient.